Model Integratif Asesment Formatif, Autentik, dan Evidence Centered Design (ECD) Abad Ke-21, Konseptualisasi dan Strategi Implementasi - Rahmi, Wifqi; Ratnaya, I Gede; Lanang Agung Parwata, I Gusti; Made Budhyani, I Dewa Ayu (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Assessment practices in Indonesian schools remain largely dominated by conventional summative evaluation, which inadequately represents reflective learning processes and mastery of 21st-century competencies. This gap highlights the suboptimal implementation of formative and authentic assessments in educational practice, as well as the lack of conceptual models capable of systematically integrating both approaches. This article aims to examine and develop an integrative assessment model that combines three key approaches: formative assessment, authentic assessment, and Evidence-Centered Design (ECD), as a strategic framework to strengthen assessment practices for 21st-century learning. This study is based on a conceptual synthesis of more than 20 national and international sources. A narrative review approach is employed, focusing on the three main approaches: formative assessment, authentic assessment, and ECD. The results of the review produce an integrative assessment model articulated in the Claim–Task–Evidence–Feedback syntax, which merges competency mapping (claim), real-world task design (task), student performance evidence collection (evidence), and continuous formative feedback (feedback). This model not only unifies the strengths of the three approaches but also offers practical solutions to the challenges of assessment implementation in Indonesia through practice-based training, integration into instructional planning, and support from technical policy frameworks. The article contributes to the advancement of assessment design that is pedagogically valid, contextually relevant, and instrumental in driving learning transformation.